Native kidney BK virus nephropathy, a systematic review. Issue 4 (11th May 2019) - Shah, Ankur; Kumar, Vinayak; Palmer, Matthew B.; Trofe‐Clark, Jennifer; Laskin, Benjamin; Sawinski, Deirdre; Hogan, Jonathan J.
Abstract: Background: There is a growing base of literature describing BK nephropathy (BKVN) in patients outside of the setting of kidney transplant. Previous systematic reviews of the literature have been limited by methodology or by the scope of patients included. Study Design and Methods: Systematic Review (Prospero # CRD42018088524). Setting & Population: Patients without kidney transplant who had biopsy‐proven BKVN. Selection Criteria for Studies: Full‐text articles that describe native BKVN patient cases. Analytical Approach: Descriptive synthesis. Results: The search identified 630 unique articles of which 51 were included in the final review. Sixty‐five cases (including two new cases presented in this review) were identified, all but one occurred in the setting of known immunosuppression. Limitations: The primary limitation was the exclusion of studies that did not fulfill the stringent review criteria. We excluded reports with only a clinical diagnosis of BKVN, such as those with viruria and/or viremia without biopsy. Conclusions: As of May 2018, there are 65 reported cases of BKVN in native kidneys. This represents the most comprehensive description of biopsy‐proven BKVN in native kidneys to date. Evaluation for BK nephropathy should be considered in immunocompromised patients who exhibit unexplained renal failure.